Asiagomphus reinhardti sp. nov. (Odonata, Gomphidae) from eastern Cambodia and southern Laos - Kosterin, Oleg E.; Yokoi, Naoto (Zootaxa, 2016)
Asiagomphus reinhardti sp. nov. is described by two males from Annamense Mountains in eastern Cambodia (holotype: Cambodia, Mondulkiri Province, the left tributary of the main river downstream from Buu Sraa Waterfall, 12°34’01–19’’ N 107°24’50’’–25’03’’ E, ca 450 m a.s.l., 15 vi 2014, RMNH) and southern Laos. The species is characterised by a large caudal lobe on S10 in males and a blunt medial lateroventral projection at cercus.